1998
DOI: 10.1038/bjc.1998.105
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of interleukin 12 on mouse haemangiosarcomas is not associated with an increased anti-tumour cytotoxic T-lymphocyte activity

Abstract: Summary In syngeneic mice, the H5V polyoma middle-T oncogene-transformed endothelioma cell line induces Kaposi's sarcoma-like cavernous haemangiomas that regress transiently, probably because of an anti-tumour immune response, but eventually grow progressively and kill the host. To evaluate the generation of tumour-specific cytotoxic T lymphocytes (CTLs), spleen cells of tumour-bearing mice were restimulated with irradiated H5V cells in mixed leucocyte-tumour cell cultures. Tumour-specific CTLs were demonstrab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…17 In particular, anti -H5V hemangiosarcoma responses were found to be potentiated by IFN and IL -12, while they were abrogated by anti -T-cell antibodies. 17,19,39 Our analysis of H5V lesions expression profiles indicated that inhibition of disease development in infected mice was associated with the persistent infiltration of stagnating tumors with activated effectors (CTL and NK ) cells. Thus, we hypothesize that the parvovirus -mediated toxicity of NS1 for H5V cells stimulated intrinsic immune reaction, and that this response was intensified when the virus expressed IP -10 transgene in addition to its own NS1 and NS2 genes.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…17 In particular, anti -H5V hemangiosarcoma responses were found to be potentiated by IFN and IL -12, while they were abrogated by anti -T-cell antibodies. 17,19,39 Our analysis of H5V lesions expression profiles indicated that inhibition of disease development in infected mice was associated with the persistent infiltration of stagnating tumors with activated effectors (CTL and NK ) cells. Thus, we hypothesize that the parvovirus -mediated toxicity of NS1 for H5V cells stimulated intrinsic immune reaction, and that this response was intensified when the virus expressed IP -10 transgene in addition to its own NS1 and NS2 genes.…”
Section: Discussionmentioning
confidence: 87%
“…The antitumor protection provided by MVMp / IP -10 is quite impressive because H5V model is an especially aggressive case of experimental hemangiosarcomas, which are usually refractory to complete cure by various treatments, 16,39,44,45 with IL-12 therapy being the most successful one. 19 The antineoplastic activity of IP -10 is not without precedents, although the use of different delivery systems and tumor models precludes published data from being quantitatively compared with the present ones. The most powerful protection was observed using plasmocytoma cells stably transfected with an IP-10-expressing plasmid.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…delivery of recombinant IL-12 leads to reduced or delayed tumor growth and increased survival in transplantable, carcinogen-induced and spontaneous tumors arising in genetically modified mice. [55][56][57] It is by now clear that the antitumor effectiveness of IL-12 is dose and context dependent. 40,55,58 Delivery of IL-12 for therapeutic purposes has thus far been accomplished through direct infusion of the recombinant protein, by gene therapy using viral and non-viral vectors, electroporation, by IL-12-containing microspheres and nanoparticles or by the transfer of IL-12-overexpressing stromal and immune cell types ( Figure 2).…”
Section: Therapeutic Effects Of Il-12 In Preclinical Modelsmentioning
confidence: 99%
“…This may explain why the single therapy with rIL‐2 did not show any remarkable effects. On the other hand, IL‐12 reportedly has effects on AS, and it also induces LAK cell activity, but these effects are not interrupted by IL‐4 14–16 . According to these facts, we assume that OK‐432 may induce LAK activation directly and via IL‐12.…”
Section: Discussionmentioning
confidence: 70%